On a Common Currency for the GCC Countries - Jadresic, Esteban (IMF Policy Discussion Papers; Policy Discussion Paper, 2002)
This paper assesses the eventual replacement of the currencies of the GCC countries with a common currency. It concludes that a properly implemented currency union may contribute to enhance economic efficiency in the region, deepen regional integration, and develop its non-oil economy. However, it cautions that a currency union should be seen as only one component of a much broader integration effort. This should include the removal of the distortions that inhibit intraregional trade and investment, agreements on policy frameworks to ensure macroeconomic stability, and further political integration. The paper also addresses the choice of exchange rate arrangement for the unified currency.